Bach’s Well‐Tempered Clavier: Pedagogical Approaches and the Different Styles of Preludes (Per Musi, 2018)
The present article discusses pedagogical aspects aiming to contribute to teaching and learning Bach’s Preludes of the Well‐Tempered Clavier. Section one presents a review of the prelude as a musical genre and the different styles that influenced the Well‐Tempered Clavier Preludes. Then, there is an analysis of selected preludes that will exemplify the variety of styles found in this work of Bach.